How does the condition of the pasture in late winter influence the plant and animal responses in the subsequent seasons? (Bioscience Journal, 2022)
This study aimed to test the hypotheses: (i) the deferred pasture with lower height in late winter has greater herbage accumulation rate (HAR) and better structure, which facilitates the animal selective grazing during the subsequent spring and summer; (ii) the mowed of high pasture in late winter improves the sward structure but decreases its HAR from the spring. Four pasture condition in late winter of Urochloa brizantha cv. Marandu were evaluated: low (24.1 cm and 2,420 kg.ha-1 of DM); low/mowed (25.2 cm and 2,198 kg.ha-1 of DM, mowed at 8.0 cm); high (49.0 cm and 3,837 kg.ha-1 of DM); and high/mowed (50.0 cm and 4,211 kg.ha-1 DM, mowed at 8.0 cm). The highest live leaf blade percentage (LLBP) and the lowest dead stem percentage (DSP) occurred in the mowed pastures. The live stem (LSP) and dead leaf blade percentages of the grazing simulation sample were higher in the high pasture. This same pattern of response occurred for apparent selectivity indices (ASI) of the live leaf blade and live stem. The ASI of the dead leaf blade was greater in the high pasture, intermediate in the mowed pastures, and lower in the low pasture. The ASI of the dead stem was lower in the low pasture. The HAR was higher in low pasture. Our results support the first hypothesis. The mowing of high pasture in late winter improves the sward structure and the animal selective grazing but does not decrease the HAR during spring and summer.